Synchronous control strategy of dual five‐level converters based on the improved SVPWM. Issue 14 (23rd October 2018) - Zhu, Junjie; Sun, Xingfa; Nie, Ziling; Rui, Wanzhi; Han, Yi; Wu, Yanhao
Abstract : This Letter has proposed a synchronous control strategy of dual five‐level converters based on the improved space vector pulse‐width modulation (SVPWM). Firstly, the main topology of the neutral point clamped (NPC) five‐level converter was introduced and its operational principle was analysed. Then, the space voltage vector diagram was offered. Considering the reduction of switching loss, the optimisation of the synthesis method of target voltage vectors and the addition of the neutral‐point potential balancing algorithm can lead to an improved SVPWM strategy for the five‐level converter. The analysis of the switching rules proves that the improved SVPWM has an advantage over the traditional three‐segment SVPWM due to its fewer times of switching. On the basis of the improved SVPWM, a synchronous control method of dual single‐phase five‐level converters is proposed to carry out a real‐time control of the dual five‐level converters through the combinational‐encoding transmission of output pulses. Thus, the synchronous control method can, to a great extent, solve the problems caused by the traditional dual five‐level independent control method, such as high hardware cost, the complexity of control, and poor synchronous performance. Simulations and experiments show that the proposed synchronous control method is feasible and effective.